Use Of Customer Relationship Management Application For Credit Union - Samuel Manurung (International Journal of Informatics and Computation, 2019)
Cooperatives are legal entities based on the principle of kinship, which consists of all members of natural or legal persons for the welfare of their members. Where most people want to open a business, it has to have a lot of capital to keep the business from running or growing. Kabanjahe The majority of the population opens a shop to meet their daily needs. The existence of a savings and loan unit can help people in the Kabanjahe region to open a business to improve the economy of people in Kabanjahe. Therefore, we need a system that is very helpful in the cooperative's transaction process. The Customer Relationship Management (CRM) application can support the notification process and simplify the cooperative payment process. This research can help cooperatives and cooperative members to conduct transactions and help members with notification of the funds spent and the date of the last payment of the paper.